Flavone-stilbene hybrids: Synthesis and evaluation as potential antimalarial agents - Bishnu Prasad Raiguru; Seetaram Mohapatra; Sabita Nayak; Dinkar Sahal; Mamta Yadav; Badri Narayan Acharya (Elsevier, 2022)
A series of flavone-stilbene-based hybrid molecules were synthesized in good to excellent yield (65-95%) via Heck coupling as the key step under conventional as well as microwave irradiation conditions. The advantages of the developed protocol involve short reaction time, high yield products obtained without the use of any additives and the ability to obtain pure compounds by recrystallization obviating the need for time-consuming column chromatography. These synthesized hybrid molecules were evaluated for their in vitro anti-plasmodial activity against chloroquine-sensitive Pf3D7 and chloroquine-resistant PfINDO strains of the malaria parasite Plasmodium falciparum using SYBR Green I assay. The compound 11g {IC50s (μM) 6.013D7, 5.67INDO} is the most promising anti-plasmodial compound in the series of flavone-stilbene hybrid molecules. The <1 Resistance indices for these potent compounds suggested their greater potency against drug-resistant PfINDO strain than against the drug-sensitive Pf3D7 strain. With their CC50s ​> ​200 ​μM the compounds were found to be non-cytotoxic towards mammalian cell line (HEK-293). The selectivity indices of >25 for the compounds suggested their specificity towards the parasite strains over mammalian cells. The covalent hybridization of flavones and stilbenes significantly enhanced their anti-plasmodial activity in comparison to individual flavone, stilbenes and their equimolar mixture. Most of the potent compounds were non-hemolytic in nature leading to the conclusion that their anti-plasmodial potency was through their actions specific to the parasite and not towards RBCs. With considerable promise as novel drugs against drug-resistant malaria parasites, it is expected these novel hybrid compounds upon further hit-to-lead optimization studies could enable us to develop new antimalarial drugs based on flavone-stilbene hybrid structures.